Determinants of electronic tax filing and employee performance among tax officers in Jordan - Alibraheem, Mohammad Haider Mahmoud (2017)
Electronic Tax Filing (ETF) in Jordan is implemented to improve the performance of the Income and Sales Tax Department (ISTD). Tax employee performance is vital to boost tax revenue collection through the efficient implementation of ETF. However, challenges regarding employees’ acceptance of new technology and their dissatisfaction of technology adoption remain a major concern. Drawing primarily upon the Unified Theory of Acceptance and Use of Technology (UTAUT), and supported by the Task-Technology-Fit theory, this study examined the impact of performance expectancy, effort expectancy, social influence, and facilitating conditions on ETF adoption with the subsequent effect of ETF adoption on tax employees’ performance. Training, Information Technology (IT) technological sophistication, and IT informational sophistication were added to extend the UTAUT theory. Also, this study examined the moderating effect of age, gender and experience on the relationships between UTAUT variables and ETF adoption. A cross- sectional survey approach was used, in which data were collected from 204 tax employees. The Partial Least Squares Method (PLS) algorithm and bootstrap techniques were used to test the hypotheses. The results supported 9 out of the 16 hypotheses. The overall findings signified positive direct relationships between performance expectancy and ETF adoption, facilitating condition and ETF adoption, training and ETF adoption, and IT technological sophistication and ETF adoption. In addition, age moderated the relationship between performance expectancy and ETF adoption, and between effort expectancy and ETF adoption while gender moderated the nexus between social influences and ETF adoption. In short, the results of this study established that performance expectancy, facilitating condition, training, and IT technological sophistication influence the adoption of ETF by tax employees regardless of age, gender and experience. The findings also indicated that there is a positive relationship between ETF adoption and employees’ performance. This implies that ETF adoption can enhance the performance of the employees.